Clinical characteristics and treatment advances in isolated axillary lymph node recurrence after breast cancer surgery - DU Xinyue, WU Siyu, LIU Guangyu (Zhongguo aizheng zazhi)
Isolated axillary recurrence (AR) after breast cancer surgery is one of the critical factors influencing patients’ prognosis. With advancements in diagnostic and therapeutic techniques, the clinical understanding of AR has progressively deepened. However, due to the low incidence of AR, systematic studies on its clinical features remain limited. High-quality clinical trials, such as ACOSOG Z0011 and AMAROS, have demonstrated that in patients with varying statuses of sentinel lymph node, axillary lymph node dissection (ALND) and sentinel lymph node dissection (SLND) provide comparable control of AR. In recent years, the trend towards de-escalation axillary surgery has advanced the development of less invasive techniques such as targeted axillary lymph node dissection. The SOUND trial further confirmed the safety and feasibility of omitting axillary surgery in patients with tumors ≤2 cm. In addition, a series of clinical studies have identified a variety of potential high-risk factors, including patient age, number of positive lymph nodes, high Ki-67 proliferation, extranodal extension, and axillary soft tissue infiltration. However, there is no broad consensus regarding the association of these factors with AR. This review comprehensively summarized the clinical characteristics, risk factors and personalized management strategies of AR, with an emphasis on the impact of different axillary surgical approaches, radiotherapy and systemic therapy on the AR risk. In addition, more high-quality clinical studies are urgently needed to further clarify prognostic factors and optimize individualized treatment strategies, so as to provide more precise management for patients.